Visual Attentional Bias Induced by Face Direction - Kou, Hui; Gong, Nanling; Yu, Wenyu; Xie, Qinhong; Bi, Taiyong (Frontiers in Psychology, 2020)
The effect of spatial cueing on eye gaze has been confirmed by a large number of studies, but the effect of spatial cueing on face direction and the impact of eye gaze on this effect are less known. In four experiments, we investigated the attentional bias induced by face direction. A modified paradigm of spatial cueing was adopted with stimuli that were static faces rotated by 90° or 45° to the left or right from the frontal view. To control the effect of eyes, face stimuli with eyes open and those with eyes closed were both used in each experiment. In Experiment 1, the facial cue (face rotated by 90°) and target were presented simultaneously, and the stimulus onset asynchrony (SOA) between the facial cue and target was set to be 300 ms, 600 ms and 900 ms in Experiments 2 (face rotated by 90°), 3 (inverted face rotated by 90°) and 4 (face rotated by 45°), respectively. The response time of detecting the target position was recorded. The spatial cueing effects were nonsignificant in Experiment 1, in which the cue and target were presented simultaneously. However, significant spatial cueing effects of face direction were found in Experiments 2 and 3, in which the upright and inverted faces rotated by 90° were adopted, respectively, in both the eyes open and eyes closed conditions. In addition, we did not find an effect of spatial cueing with the face rotated by 45° (Experiment 4). Our results indicate that face direction can bias visual attention. This effect might not be based on the holistic processing of faces.